Análisis del modelo gravitacional de comercio entre Colombia y sus principales socios comerciales para el periodo 2007-2017 (2019)
International trade for Colombia and the world is modeled by the dynamics of access to different markets. This access depends on each country's own variables such as language, sea access, transport facilities, political-administrative, cultural and economic conditions. These variables can be studied through the different versions of a gravitational equation of commerce. In this document, data is collected and an economic profile of Colombia is constructed, through export figures and the main commercial partners of Colombia are established, a version of the gravitational equation of trade is applied and the main international trade patterns are determined. It is found that, Colombia has advantages such as its strategic allies around the world, of which most of them follow the guidelines of international trade and the trend of globalization and the free market.